"Craniotomy Within Craniotomy" Technique for Safe Resection of an Intracranial Arteriovenous Malformation With Frontal Bony Erosion: 2-Dimensional Operative Video. Issue 6 (11th September 2021) - Khorasanizadeh, MirHojjat; Ravina, Kristine; Filippidis, Aristotelis; Ogilvy, Christopher S
Abstract: Surgical resection is one option in the treatment of large high-grade brain arteriovenous malformations (AVMs). Resection of AVMs with skull-eroding components can be challenging due to the risk of excessive bleeding from these components during craniotomy and bone flap removal. We present a case of a 25-yr-old woman who presented with an acute onset right-sided frontal headache. She was found to have a large, frontal Spetzler-Martin grade IV AVM with an associated dural AVM. The AVM had caused focal erosions of the right frontal bone by a venous varix traversing the region of the calvarial defect. An elective staged endovascular embolization followed by surgical resection was recommended considering the patient's young age and the large size of the AVM located in a noneloquent area. Given the high risk of intraoperative hemorrhage during the craniotomy portion of the procedure, a "craniotomy within craniotomy" approach was planned. During this approach, a small rectangle of bone, including the portion eroded by the venous varix, was left in place, while the larger bone flap surrounding it was removed for an initial approach to the AVM. The small bony piece was safely removed at later stages of resection once the arterial feeders had been reasonably obliterated. Immediate postoperative catheter angiogram demonstrated good filling of the intracranial vascular territories with no residual AVM. The patient developed mild left facial and left hand weakness postoperatively, which resolved after 2 wk of follow-up. The patient remained neurologically intact on further follow-up.